2018
DOI: 10.2147/btt.s177901
|View full text |Cite
|
Sign up to set email alerts
|

Designing of CD8<sup>+</sup> and CD8<sup>+</sup>-overlapped CD4<sup>+</sup> epitope vaccine by targeting late and early proteins of human papillomavirus

Abstract: Background and aimHuman papillomavirus (HPV) is an oncogenic agent that causes over 90% of cases of cervical cancer in the world. Currently available prophylactic vaccines are type specific and have less therapeutic efficiency. Therefore, we aimed to predict the potential species-specific and therapeutic epitopes from the protein sequences of HPV45 by using different immunoinformatics tools.MethodsInitially, we determined the antigenic potential of late (L1 and L2) and early (E1, E2, E4, E5, E6, and E7) protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 102 publications
(172 reference statements)
0
29
0
Order By: Relevance
“…In each protein, peptides with the highest binding affinity scores were determined as high-potential CTL epitope candidates (Tables 4 and 5). The analysis showed that L1 [12][13][14][15][16][17][18][19][20][21] (YLPPVPVSKV-type 16 and YLPPPSVARV-type 18), L1 460-470 (DQFPLGRKFLL-type 16), L1 461-471 (DQYPLGRKFLV-type 18), L2 [11][12][13][14][15][16][17][18][19][20] (KRASATQLYK-type 16 and KRASVTDLYK-type 18), L2 280-291 (DPDFLDIVALHR-type 16) and L2 273-284 (DSDFMDIIRLHR-type 18) epitopes had the highest binding affinity among their own protein sequences. In general, the results of three different algorithms confirmed each other.…”
Section: Prediction Of T-cell Epitopesmentioning
confidence: 99%
See 4 more Smart Citations
“…In each protein, peptides with the highest binding affinity scores were determined as high-potential CTL epitope candidates (Tables 4 and 5). The analysis showed that L1 [12][13][14][15][16][17][18][19][20][21] (YLPPVPVSKV-type 16 and YLPPPSVARV-type 18), L1 460-470 (DQFPLGRKFLL-type 16), L1 461-471 (DQYPLGRKFLV-type 18), L2 [11][12][13][14][15][16][17][18][19][20] (KRASATQLYK-type 16 and KRASVTDLYK-type 18), L2 280-291 (DPDFLDIVALHR-type 16) and L2 273-284 (DSDFMDIIRLHR-type 18) epitopes had the highest binding affinity among their own protein sequences. In general, the results of three different algorithms confirmed each other.…”
Section: Prediction Of T-cell Epitopesmentioning
confidence: 99%
“…Since a suitable T-cell epitope should be predicted to bind to different HLA alleles, epitopes with the maximum number of binding HLA-DR alleles were selected as high-potential helper T-cell epitope candidates. Among predicted epitopes, L1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (EATVYLPPVPVSKVV-type 16), L1 95-111 (TQRLVWACVGVEVGRGQ-type 16 and TQRLVWACAGVEIGRGQ-type 18), L1 416-430 (DTYRFVTSQAIACQK-type 16), L1 417-431 (DTYRFVQSVAITCQK-type 18), L2 [100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] (DPSIVTLIEDSSVVTSGAP-type 16), L2 281-297 (PDFLDIVALHRPALTSR-type 16) and L2 [274][275][276][277][278][279][280][281][282][283][284][285][286][287][288][289][290] (SDFMDIIRLHRPALTSR-type 18) had the highest scores of binding affinity. Also, the sequence of all the epitopes were well ...…”
Section: Prediction Of T-cell Epitopesmentioning
confidence: 99%
See 3 more Smart Citations